Exploring Trend of Cash Waqf Research: A Bibliometric Analysis - Nurhasanah, Elis (FEB Universitas Sultan Ageng Tirtayasa, 2025)
This study examines research performance in the field of cash waqf by analyzing the most contributing authors, research themes, citations, and journals that frequently publish on the cash waqf topic. This study adopted a bibliometric approach, analyzing 215 research articles indexed in Scopus. The exported data was processed and analyzed using RStudio and bibliometric tools such as Bibliometric and Biblioshiny to identify the main keywords, trends, and development of research themes in the field. The journal that dominates articles about cash waqf is ISRA International Journal of Islamic Finance. The most prolific author in this field is Sukmana R with 10 papers, followed by Bulut M. University Sains Islam Malaysia is the top affiliate with 27 publications. In terms of citations, Malaysia ranked first with 718 citations, while Indonesia came second with 370 citations. Indonesia also showed the highest level of international collaboration in cash waqf research. Mandaville's (1979) work has the highest number of global citations in the cash waqf field, with 128 citations.